2013
DOI: 10.1186/1471-2458-13-319
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and spousal mental distress in a population sample: the nord-trøndelag health study

Abstract: BackgroundIt is a widely held notion that alcohol abuse is related to mental distress in the spouse. Research has substantiated this notion by showing a tendency for spouses of alcohol abusers to experience more mental distress than spouses of non-abusers. However, the picture seems to be more complex, as some results do not show a significant effect or even less mental distress among spouses of alcohol abusers with the highest alcohol consumption. The present study investigates the association between spousal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…This relationship was strengthened by the nearness of the relationship and presence of adverse consequences of drinking [18]. However, one study conducted in Norway showed that respondents only reported higher levels of depression and anxiety if their drinking patterns were different from those of their partners [19]. However, these results may not be very relevant for comparison as none of the women in this study reported consuming any alcohol.…”
Section: Discussionmentioning
confidence: 76%
“…This relationship was strengthened by the nearness of the relationship and presence of adverse consequences of drinking [18]. However, one study conducted in Norway showed that respondents only reported higher levels of depression and anxiety if their drinking patterns were different from those of their partners [19]. However, these results may not be very relevant for comparison as none of the women in this study reported consuming any alcohol.…”
Section: Discussionmentioning
confidence: 76%
“…Divorce is more likely in couples who consume large amounts of alcohol. One group of researchers found that high alcohol consumption not only increased the likelihood of divorce, but exacerbated the difficulties of the mental healing process following the divorce (Rognmo, Torvik, Røysamb & Tambs, 2013). Research by Kenneth et al (2007) also shows how common it is for couples to separate in the early years of their relationship due to substance abuse within the relationship.…”
Section: The Psychosocial Impact Of Substance-use Disorder On Family mentioning
confidence: 99%
“…Population-based studies have shown that CMD are more prevalent among the poor, unemployed, persons with low social support or who have experienced stressful life events, alcohol and drug consumers, and those with less years of schooling [ 7 - 9 ]. Gender differences are also consistent in the literature [ 10 , 11 ], with anxiety and mood disorders being approximately twice as common in women as in men [ 4 ], regardless if occurring in higher or lower income countries [ 12 ].…”
Section: Introductionmentioning
confidence: 99%